A "boundedness implies convergence" principle and its applications to collapsing estimates in Kähler geometry. (May 2021) - Jian, Wangjian; Shi, Yalong
Abstract: We establish a general "boundedness implies convergence" principle for a family of evolving Riemannian metrics. We then apply this principle to collapsing Calabi–Yau metrics and normalized Kähler–Ricci flows on minimal models to obtain convergence results.